Tingkat Kepuasan Siswa dalam Peminatan Program Studi pada Kelas XI IPA SMA Negeri 5 Semarang Tahun Ajaran 2015/2016 - Fazar, Mochammad (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The research had been done based on the phenomenon in SMA N 5 Semarang which show the high number of student ho were unsatisfied in the service of interest accorded to the result of interview and observation in obtaining the initial data of the students of XI IPA SMA N 5 Semarang. The aim of the research is to find out the satisfactory level of the student in calssifying their interest on the student of XI IPA SMA N 5 Semarang. The research is included survey research which used the random sampling technique. The collecting data technique used is interview and psychological scale. The validity test used the formula of excel program. The reliability test used the split half formula from Spearman Brown. The result of this research is the satisfactory level of the students was on the satisfied enough criteria with 56,34% percentage. With the indicator of reliability reaches 70,52%, responsiveness 21,15%, assurance 67,04%, and emphaty reaches 66,63%. Because of that the school counselors are hope to do some evaluations in order to improve the servive of interest in school and also the headmaster should give the supporting policy for the optimal counseling service implementation.